Construction technology 2: Industrial and commercial building - Riley, Mike; Cotgrave, Alison (New York Palgrave, 2014)
A new edition of this popular undergraduate textbook for the study of industrial and commercial building. This third edition is thoroughly revised including new material on sustainable construction, Building Information Modelling (BIM) and sustainable building services.
Keywords: PREPARING TO BUILD; BUILDING SUBSTRUCTURE;BUILDING SUPERSTRUCTURE; SUSTAINABLE BUILDING SERVICES; BUILDING CONSTRUCTION (BT-CON)